Evaluation of Complications Following a Trans-masseteric Antero-parotid Approach for Patients with Sub-condylar Fractures of Their Temporomandibular Joint. A Retrospective Study - Machoň, Vladimír; Desai, Avni; Levorová, Jitka; Hirjak, Dušan; Brizman, Eitan; Foltán, René (Prague medical report, 2019)
Sub-condylar fractures of the temporomandibular joint can be treated by an extraoral or intraoral approach. Trans-masseteric antero-parotid approach (TMAP) is an extraoral approach utilising a retromandibular incision. The authors evaluated patients' status and any complications of using TMAP from the years 2013-2017. There were 39 patients (44 fractures). When using TMAP, in 43 fractures the fragments were favourably positioned, in one case the position was compromised. Of the complications, postoperative palsy of the facial nerve was reported 6.8% - in all cases this was only temporary. Late occlusion had an equal number of complications (in 2 cases this was as a result of an infectious complication of the wound, and in 2 cases due to resorption of the proximal fragment). Muscular pain and dysfunction of the temporomandibular joint following trauma were observed consistently in 6.8% of patients. Sialocoele, a non-conforming scar, and infectious complications were observed in 4.5% of patients. TMAP allows rapid surgical performance, with a good view for perfect repositioning and fixation of fragments of sub-condylar fractures of the temporomandibular joint. The complications associated with this approach are, for the most part, temporary, the aesthetic handicap of a scar is considered by patients to be acceptable. Overall, it is possible to evaluate retromandibular TMAP as safe, and the authors recommended it for treatment of sub-condylar fractures of the mandible.
Keywords: Masseter Muscle; Mandibular Fractures; výsledek terapie; Temporomandibular Joint; Mandibular Condyle; lidé; Mandible; Trans-masseteric antero-parotid approach; pooperační komplikace; Treatment Outcome; Sub-condylar fractures; retrospektivní studie; Postoperative Complications; temporomandibulární kloub; musculus masseter; processus condylaris mandibulae; fraktury mandibuly; Retrospective Studies; Parotid Gland; parotis; Humans